2001
DOI: 10.1254/jjp.85.291
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Carbachol-Activated Nonselective Cation Channels at the Single Channel Level in Guinea Pig Gastric Myocytes

Abstract: ABSTRACT-We investigated the properties of carbachol (CCh)-activated nonselective cation channels (NSCCCh) at the single channel level in the gastric myocytes of guinea pigs using a magnified whole-cell mode or an outside-out mode. The channel activity (NPo) recorded in a magnified whole-cell mode increased with depolarization (from -120 to -20 mV) and had the half activation potential of -81 mV under the symmetrical 140 mM Cs + condition. with 33% Na + . These data suggested that the extracellular monovalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…We have also showed that G o type among GTP-binding proteins is responsible for activating the channel (22). Fourth, the unitary conductance was ϳ25-30 pS (3,13,18,42). The open probability is modulated by extracellular monovalent cation (18).…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…We have also showed that G o type among GTP-binding proteins is responsible for activating the channel (22). Fourth, the unitary conductance was ϳ25-30 pS (3,13,18,42). The open probability is modulated by extracellular monovalent cation (18).…”
mentioning
confidence: 71%
“…Another property of NSCC CCh is the dependence upon extracellular Ca 2ϩ concentration (12,18). The NSCC was also modulated by extracellular calcium in murine stomach (Fig.…”
Section: Rt-pcr and Expression Of Trp Channelsmentioning
confidence: 94%
See 3 more Smart Citations